Sharia Marketing Strategy And The Role Of Social Networking (Social Networking) On Wooden Pallet Smes In Purwokerto - Asrof Dzahuri; Muhamad Annas (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
sector in Indonesia is facing pressure double : acceleration demanding digital transformation adaptation strategy marketing, and weakening dimensions ethics business in the increasingly digital space competitive. Research This aim analyze in a way comprehensive implementation strategy marketing sharia, pattern utilization network social, as well as constraint strategic issues faced by pallet MSMEs wood in Purwokerto . Research use approach qualitative with design studies cases in three UD Sukses business units Independent, UD Berkah Mandiri, and UD Estu Independent selected through purposive sampling. Data collection was carried out through interview in-depth semi- structured, observation participatory, and documentation systematic social media content. Data analysis using approach thematic based category theoretical , reinforced with IFAS and EFAS matrices based on framework Rangkuti SWOT analysis as well as Barney's Resource-Based View (RBV) framework. Research results shows : (1) principles Shiddiq , Amanah , Tabligh , and Fathanah implemented in a way consistent as foundation all over activity marketing; (2) networking social utilized in a way differentiated as instrument promotion, communication relational, and expansion network business; and (3) limitations digital HR capabilities and competition No Healthy is obstacle challenging dominant consistency mark Sharia. The IFAS matrix ( score 2.65) and EFAS ( score 2.70) show position strategic business is in Quadrant I, where integrity ethics sharia proven as an intangible competitive asset that is valuable, rare, and difficult to obtain imitated competitors.